The religious phenomenon and politics in the political movement MIRA (2020)
The article reveals the general observation that was made within the Ministerial Church of Jesus Christ International and the existing relationship with the MIRA political group. The religious and political manifestations, as well as the aspects inherent in the life of every human being are made known. The technique used was a structured interview and the active participation of those who participated part in the study in question. It can be shown that the contemporary human being points precisely as established by the word of God, to a congruence between his political and ideological positions with respect to his religious belief and the living manifestation of his faith. However, you cannot be one in politics and another in religion.